Treatment of Presumed Hyperkalemia in the Prehospital Setting. Issue 5 (4th October 2022) - McArthur, Robert; Rafique, Zubaid; Ward, Brad; Rodriguez, Luis; Dickson, Robert; Patrick, Casey
Abstract: Introduction: Hyperkalemia (HK) is common and potentially a life-threatening condition. If untreated, HK can progress to ventricular arrhythmia and cardiac arrest. Early treatment reduces mortality in HK. This study evaluates a novel protocol for identification and empiric management of presumed HK in the prehospital setting. Methods: This was a retrospective, observational chart review of a single, large, suburban Emergency Medical Services (EMS) system. Patients treated for presumed HK, with both a clinical concern for HK and electrocardiogram (ECG) changes consistent with HK, from February 2018 through February 2021 were eligible for inclusion. Patients were excluded if found to be in cardiac arrest on EMS arrival. Empiric treatment of HK included administration of calcium, sodium bicarbonate, and albuterol. Post-treatment, patients were placed on cardiac monitoring and adverse events recorded enroute to receiving hospital. Protocol compliance was assessed by two independent reviewers. Serum potassium (K) level was obtained from hospital medical records. Results: A total of 582 patients were treated for HK, of which 533 patients were excluded due to cardiac arrest prior to EMS arrival. The remaining 48 patients included in the analysis had a mean age of 56 (SD = 20) years and were 60.4% (n = 29) male with 77.1% (n = 37) Caucasian, 10.4% (n = 5) African American, and 12.5% (n = 6) Hispanic. Initial blood draw at the receiving facilities showed K >5.0mEq/L in 22 (45.8%), K of 3.5-5.0mEq/L in 23 (47.9%), and K <3.5mEq/L in three patients (6.3%). Independent review of the EMS ECG found the presence of hyperkalemic-related change in 43 (89.6%) cases, and five (10.4%) patients did not meet criteria for treatment due to lack of either appropriate ECG findings or clinical suspicion. No episodes of unstable tachyarrhythmia or cardiac arrest occurred during EMS treatment or transport. Conclusion: The study evaluated a novel protocol for detecting and managing HK in the prehospital setting. It is feasible for EMS crews to administer this protocol, although a larger study is needed to make the results generalizable.